Improving Children's Creativity through Activities Ecoprint Batik Based on Local Wisdom - Saputri, Elvi Helmi; Wirman, Asdi; Yeni, Indra; Anggraini, Vivi (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
Early childhood creativity is crucial to discuss because it can increase children's self-confidence and explore the various potentials that exist in children, especially during this golden age. It was found that early childhood creativity in one of the kindergarten educational institutions was still relatively lacking because the activities carried out to stimulate creativity were less varied. One way for children's creativity to increase and develop, it is necessary to have activities so that they can show their creativity. There are various activities to make children's creative power increase, one of which is with ecoprint batik activities. This study aims to analyze the effect of ecoprint batik activities on children's creativity. The method used is quantitative research with the Pre-Experimental type, and the research design uses “One-Group Pretest-Posttest Design”. The sample studied was group B as many as 10 children. Based on the results of the study, it can be concluded that the ability of children's creativity in class B2 using ecoprint batik activities, the highest value is 31 and the lowest value is 20, with an average value of 26.1. Based on the value obtained sig (2-tailed) in the B1 class post-test t test 0.00 <0.05, so it is stated to be significant (there is a difference). Thus, researchers can conclude that the hypothesis (Ha) in this study is accepted, namely that there is an effect of batik activities on children's creativity abilities by implementing experimental ecoprint batik activities based on local wisdom.